UKRAINE’S INTERACTION WITH INTERNATIONAL MONETARY FINANCIAL ORGANIZATIONS - Rodina , O. H.; Daniv, R.V. (The actual problems of regional economy development, 2022)
The article is devoted to the study of Ukraine's cooperation with international financial organizations, analysis of positive and negative aspects of cooperation and identification of specific levers to improve the efficiency of attracted credit resources of international monetary and financial organizations in the national economy, special attention is paid to the analysis of the following organizations: the International Monetary Fund, the World Bank, the International Bank for Reconstruction and Development and the European Bank for Reconstruction and Development. On the way to integration into the world economic space, Ukraine is establishing cooperation with various international organizations, including financial ones. Monetary and financial organizations play an important role both in regulating the world economy and in the economic development of individual countries, namely their financing. As a result, the issue of Ukraine's relations with international financial organizations is relevant, and his research is of considerable scientific interest. The following methods were used in the research process: systemic and structural-functional - to clarify the nature and components of international monetary and financial organizations; classifications - in the study of types of organizations on various grounds; analysis and synthesis - to clarify the place and role of key international organizations in the structure of international monetary and financial organizations; comparative - when conducting a comparative analysis of the activities of the International Monetary Fund, the World Bank Group and the European Bank for Reconstruction and Development; empirical - in the study of the practice and performance of organizations in Ukraine; graphic - in order to clearly display the results of analytics. International financial organizations have a significant impact on improving Ukraine's economic situation, Ukraine's cooperation with international monetary and financial organizations helps to increase macroeconomic stabilization indicators, create a competitive market environment, stabilize the national currency, strengthen the investment process, develop the private sector. It is substantiated that international monetary and financial organizations play a key role in regulating the global financial system and lending to socio-economic development of the world. The investment and credit activity of the IMF in Ukraine is analyzed. The structure and dynamics of financing projects of international monetary and financial organizations in Ukraine are studied. The practical significance is that the directions of optimization of relations between Ukraine and international monetary and financial organizations proposed in the bachelor's thesis are recommended for writing reports and other scientific publications in terms of Ukraine's cooperation with MFIs and its future prospects.